Internal audit of costs on fixed assets repair - M.Yu. Samchyk (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The article focuses on the approaches to the process and methods of expenditure audit on repair and modernization of fixed assets and the author considers that there is no single approach to understanding the issue. The author improves the organizational and methodological support of internal audit of expenditures on the fixed assets repair and modernization that forms the accurate information for management repair and modernization of fixed assets. The paper specifies the goals and objectives of internal expenditures on repair and modernization of fixed assets, depending on the sources of such facilities to the company, allowing the author to determine the documentary control methods to be applied by an auditor to perform each task. The article determines the areas of risk components of internal control that can lead to ineffective implementation of authority by officials of an enterprise in the process of fixed assets repair, which can cause inefficient use of resources and, consequently, decrease in the efficiency of the work of fixed assets repair and modernization. The author proposes the list of auditor’s questions to assess the internal control system in the repair of fixed assets and these questions will help identify the significant drawbacks of control means.